Protecting Persons While Protecting the People Second Annual Workshop on Information Privacy and National Security, ISIPS 2008, New Brunswick, NJ, USA, May 12, 2008. Revised Selected Papers - Gal, Cecilia S.; Kantor, Paul B.; Lesk, Michael E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
The Second Annual Workshop on Privacy and Security, organized by the Center for Interdisciplinary Studies in Information Privacy and Security of the School of C- munication and Information at Rutgers University, was held on May 12, 2008 at the Hyatt Regency, New Brunswick, New Jersey, USA. A few of the papers in this volume were produced through a multi-step process. First, we recorded the talk given by each author at the workshop in May 2008. Next, we transcribed the recording. The authors then produced a draft of their paper from these transcriptions, refining each draft until the final version. Although the papers are not verbatim transcriptions of the talks given, some do retain the informal and conv- sational quality of the presentations. In one instance we have included some material from the question-and-answer period after the talk, since the material covered proved to be relevant and interesting. The majority of authors, however, preferred to include a more formal paper based on the material presented at the workshop.
The Challenges of Seeking Security While Respecting Privacy -- The Challenges of Seeking Security While Respecting Privacy -- Section One: Statement of the Problem -- Intelligence Policy and the Science of Intelligence -- Cyber Security: Assessing Our Vulnerabilities and Developing an Effective Defense -- Intelligence, Dataveillance, and Information Privacy -- Results of Workshops on Privacy Protection Technologies -- Words Matter: Privacy, Security, and Related Terms -- Section Two: Theoretical Approaches to the Problem -- kACTUS 2: Privacy Preserving in Classification Tasks Using k-Anonymity -- Valid Statistical Analysis for Logistic Regression with Multiple Sources -- Section Three: Practical Approaches to the Problem -- Suspicious Activity Reporting (SAR) -- Stable Statistics of the Blogograph -- Privacy-Preserving Accountable Accuracy Management Systems (PAAMS) -- On the Statistical Dependency of Identity Theft on Demographics.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Data mining; Biometrics (Biology).; Computers and civilization; Computers; Law and legislation; Computer Science; Computers and Society; Data Encryption; Data Mining and Knowledge Discovery; Legal Aspects of Computing; Systems and Data Security; Biometrics; Electronic books